Răspuns :
Răspuns:
Explicație pas cu pas:
a) √(4/9)-√(48/45)+√(49/9)=2/3-√(4²·3/3²·5)+7/3=2/3+7/3-4√3/3√5=9/3-4√15/3·5=9/3-4√15/3·5=(9·5-4√15)/15=(45-4√15)/15
b) √(1000/288)-√(180/9)+√(180/256)=√(10²·10/12²·2)-√20+√(2²·3²·5/16²)=
10/12(√10/2)-√(2²·5)+2·3√5/16=5/6√(10/2)-2·√5+3√5/8=
5√5/6-2√5+3√5/8=(4·5√5-2·24√5+3·3√5)/24=
(20√5-48√5+9√5)/24=-19√5/24
c) √(4 23/49)+√(1 1/49)+√(2 30/49)-√(3 15/49)= √(219/49)+√(50/49)+√(128/49)-√(162/49)=
√219/7+√(5²·2)/7+√(8²·2)/7-√9²·2)/7= (√219+5√2+8√2-9√2)/7=
(√219+4√2)/7
d) √(1 8/100)-√(1 368/400)+√(36 12/16)-√(1 11/16)=
√(108/100)-√(768/400)+√(588/16)-√(27/16)=
√(2²·3²·3/10²)-√(2²·8²·3/2²·10²)+√(2²·7²·3/4²)-√(3²·3/4²)=
2·3√3/10-2·8√3/2·10+2·7√3/4-3√3/4=3√3/5-4√3/5+7√3/2-3√3/4=
-√3/5+7√3/2-3√3/4=(-4√3+70√3-15√3)/20=51√3/20